THE ROLE OF LAW AND SHARIAH GOVERNANCE IN ISLAMIC FINANCE TOWARDS SOCIAL JUSTICE IN DIVERSITY - Ruzian Markom (Fakultas Hukum, Universitas Diponegoro, 2018)
Comprehensive law and Shariah governance framework are important in ensuring the sustainability of Islamic financial goal. Both elements contributed in the process of social justice in diversity between the industry and the society. This article is aimed to discuss on the role of law and Shariah governance in Islamic finance towards social justice in diversity. It defined the meaning of laws, Shariah governance and social justice in diversity in the context of Islamic finance. Then, it analysed the challenges of Islamic finance in promoting social justice in diversity. Finally, in resolving the challenges, it is recommended to adopt the six key areas laid down in the World Global Report 2016.